Arrow on domain conditions: a fruitful road to travel. - Barberà, Salvador; Berga, Dolors; Moreno-Jiménez, Bernardo (Springer, 2020)
We stress the importance that Arrow attached to studying the role of domain conditions in determining the validity of his impossibility theorem, a subject to which he devoted two chapters of Social Choice and Individual Values. Then we partially survey recent results about the role of domain conditions on the possibility to design satisfactory aggregation rules and social choice functions, as a proof of the continued vitality of this subject, that he pioneered, as he did with so many others.
Keywords: Juegos, Teoría de; Toma de decisiones (Estadística); Paradojas; Social welfare functions; Social choice functions; Restricted domains; Single peakedness; Selfishness; Dictatorship; Connectedness; Arrow's Impossibiltity Theorem